Current management of children with acute otitis media: a feasibility survey for a pragmatic study - Respati Wulansari Ranakusuma; Amanda R. McCullough; Elaine M. Beller; Christopher B. Del Mar; Eka Dian Safitri; Yupitri Pitoyo; Widyaningsih Widyaningsih (Indonesian Pediatric Society, 2019)
Background Acute otitis media (AOM) is a common self-limiting infection where antibiotics confer limited benefit. Other treatments, such as anti-inflammatory agents have been proposed as an alternative to antibiotics, but no high-quality clinical trials have tested this. Objective To identify current AOM management practices among Indonesian clinicians. We also required this information for our proposed corticosteroids clinical trial for AOM. Methods This cross-sectional study surveyed a convenience sample of general practitioners (GPs), pediatricians, and Ear-Nose-Throat (ENT) specialists in Jakarta, Depok, and Bekasi. We addressed their current AOM management practices and willingness to participate in a future trial on corticosteroids. Results We distributed 2,694 questionnaires through conferences, primary care/hospital visits, and by mail-list group. Of 492 questionnaires received (response rate 18%), 352 were from eligible clinicians. Most clinicians diagnosed AOM by using an otoscope (64-91%). Tympanometry was used by a quarter of ENT specialists. Amoxicillin-clavulanate was the most common antibiotic for AOM, prescribed by pediatricians and ENT specialists, whilst most GPs prescribed amoxicillin. Clinical scenarios indicated most ENT specialists (88%) would prescribe antibiotics and most pediatricians (54%) would choose expectant observation by withholding antibiotics for mild AOM. Almost half of clinicians would consider using corticosteroids in a trial. Conclusion Most clinicians would prescribe antibiotics for mild AOM. However, slightly over half of pediatricians would solely choose expectant observation. Adequate numbers of potential participating clinicians, who would consider using corticosteroids, make our proposed corticosteroids trial for AOM feasible. We found gaps between clinical practice and evidence requiring further investigation to improve AOM management in Indonesia.